Pengaruh Tingkat Risiko Pembiayaan terhadap Profitabilitas Bank Umum Syariah - Ilham Wahyudi; Yogi Franata; Tomi Hartawan; Andang Sunarto; Aan Shar (BUDGETING : Journal of Business, Management and Accounting, 2022)
This study aims to determine the level of financing risk to the profitability of Islamic commercial banks. This study uses data from the financial statements of Islamic commercial banks that have been audited and published to the public through the official website of the financial services authority. The author uses a quantitative descriptive type of research; the analysis method in this study is a simple linear regression analysis. The sample determination technique used with purposive sampling techniques is to select samples based on certain criteria based on the purpose of the study. The results showed that there was a significant negative relationship between NPF and ROA. The relationship is a cause-and-effect relationship, so the ROA value is inversely proportional to the NPF. In this study, the size of the ROA value was influenced by NPF. It can be concluded from this study that there is a significant negative relationship between NPF and ROA. The relationship is a cause-and-effect relationship, so the ROA value is inversely proportional to the NPF. Keywords: Profitability, Financing Risk level